Scleroma of the Nose and Pharynx - DiBartolomeo, Joseph R. (1976)
Scleroma of the respiratory tract was first recognized just over a century ago. The disease is endemic in a number of North African, Central American and Latin American countries. However, it has been only rarely seen in the United States. The progression of scleroma takes place through three stages. The first stage of rhinitis has an early catarrhal phase which progresses to one of atrophic rhinitis. The second stage is seen as a proliferative granulomatous growth which obliterates the nasal fossae. The third cicatricial stage is usually accompanied by pronounced scarring and retraction of the tissues involved. Because of the increased ease of international travel by both sea and air, more cases can be expected to occur in the United States. This paper is presented to alert physicians to suspect scleroma in any case of granulomatous disease of the respiratory tract.